Sex Chromosome Evolution in Amniotes: Applications for Bacterial Artificial Chromosome Libraries - Janes, Daniel E. (Hindawi Publishing Corporation, 2011)
Variability among sex chromosome pairs in amniotes denotes a dynamic history. Since amniotes diverged from a common ancestor, their sex chromosome pairs and, more broadly, sex-determining mechanisms have changed reversibly and frequently. These changes have been studied and characterized through the use of many tools and experimental approaches but perhaps most effectively through applications for bacterial artificial chromosome (BAC) libraries. Individual BAC clones carry 100–200 kb of sequence from one individual of a target species that can be isolated by screening, mapped onto karyotypes, and sequenced. With these techniques, researchers have identified differences and similarities in sex chromosome content and organization across amniotes and have addressed hypotheses regarding the frequency and direction of past changes. Here, we review studies of sex chromosome evolution in amniotes and the ways in which the field of research has been affected by the advent of BAC libraries.